Hypoglycemic and antioxidant activity of polyphenol glycoside catalyzed by transglycosylation reaction of cyclodextrin glucanotransferase derived from trichoderma viride - Sohaib Nazir (2018)
Present study was conducted to evaluate the ability ofTrichoderma viridae as a source of cyclodextrin glucanotransferase (CGTase) that has shown transglycosylation activity in the presence of polyphenolic constituents extracted from Moringa oleifera leaves as its acceptor to catalyze synthesis of polyphenolic glycosides as transglycosylation products. The study had indicated that some commercial substrates such as corn flour, wheat flour, rice flour and cassava flour could be utilized as potential substrates to synthesis transfer products in the presence of polyphenolic acceptors extracted from seaweed, clove, ginger, torch ginger and star anise. The enzymatically synthesized polyphenolic glycosides were then purified using octa-dodecyl-functionalized silica gel column chromatography prior to analysis using high performance liquid chromatography (HPLC) and identified using nuclear magnetic resonance (NMR) spectroscopy. The result of HPLC analysis presented that the isolated transfer products had retention times at 1.446, 1.431, and 1.474, respectively, compared to the retention time of arbutin (1.474) that was applied as an external authentic standard for polyphenol glycoside. Moreover, observation using 1H NMR as well as 13C NMR showed that structures of the transglycosylation products were identified as gallic acid-4-O-,8-Dglucopyranoside, ellagic acid-4-O-,8-D-glucopyranoside, and catechin-4'-O-,8-Dglucopyranoside, respectively. Ellagic acid-4-O-,8-D-glucopyranoside (EAGP) was evaluated for its antioxidant properties as it had the same RF value as compared to arbutin and was subjected to assess its antioxidant potential using various in vitro analyses. ICso value of EAGP for DPPH free radical scavenging test was calculated as 46.12µg/ml as compared to the standards ascorbic acid (35.96µg/ml), BHT (39.73µg/ml) and a-tocopherol (42.62µg/ml), respectively. In ABTS+ radical scavenging assay, ICso value for EAGP was recorded as 64.0lµg/ml as compared to ascorbic acid (30.13µg/ml), BHT (38.09µg/ml) and a-tocopherol (54.84µg/ml) respectively. The ICso value of EAGP as percentage of metal chelating ability was determined as 45.42µg/ml where EDTA as standard showed 28.24µg/ml. In H2O2 radical scavenging assay, ICso value of EAGP was found to be 51.90µg/ml while BHT and a-tocopherol were 44.18µg/ml and 47.18µg/ml, respectively. The assays demonstrated that the presence of moderate antioxidant properties of enzymatically synthesized EAGP as compared to the ascorbic acid, BHT and er tocopherol. Furthermore, hypolipidemic and antidiabetic effect of enzymatically synthesized EAGP in normal and alloxan- induced diabetic rats were investigated. Diabetes was induced in rats by a single dose administration of alloxan (150 mg/kg, i.p.) for 28 days. Blood glucose levels were determined at day 0 until day 28 of treatment and blood glucose levels on four day after treatment with alloxan were significant (p<0.05) increasing in all diabetic rats as compared to normal control rats. At day 12, three different dosages of EAGP at concentration 100 mg/kg, 200 mg/kg, 400 mg/kg of body weight showed significant decrease (5-7%) (p<0.05) in blood glucose levels in alloxan induced diabetic rats as compared to untreated diabetic group. All the hyperglycemic groups which were treated with various dosages of EAGP recorded significantly (p<0.05) lower biochemical parameters (Cholesterol, triglycerides, HDL, LDL, creatinine, urea, alkaline phosphatase) of blood serum as compared to untreated diabetic group. Pancreatic tissue analysis of alloxan induced diabetic groups exhibited significant (p<0.05) reduction in catalase activity, GSH levels and lipid peroxidation (MDA) levels as compared to normal control group, while treated diabetic groups showed significant (p<0.05) elevation as compared to untreated diabetic group and activities were quite near to normal rats. In brief, the results of the recent research discovered that the hypoglycemic and hypolipidemic potentials of enzymatically synthesized polyphenol glycoside (EAGP) might be attributed to its free radical scavenging and antioxidant properties. Hence, it is resolved that EAGP may be suitable in the prevention of hyperglycemic complications linked with oxidative stress.